(untitled) (International Journal of Environmental Sciences, 2025)
The current study aims to explore the efficiency of blended learning on developing hand embroidery. The participants were 62 students from the College of Education at Najran University. They were divided randomly into two groups (experimental and control), each group included 31students. Where the experimental group studied the "hand embroidery" course through the blended learning, and the control group studied the same course in the traditional way. A product evaluation card was used as a tool to achieve the objective of the study. The study found the effectiveness of blended learning in enhancing the students' skills in hand embroidery